1985
DOI: 10.7863/jum.1985.4.6.293
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of contralateral ovulation in ectopic pregnancy.

Abstract: Patients with an ectopic pregnancy were studied for documentation of the site of ovulation in order to determine the frequency with which controlateral ovulation and ovum transport occurs. Analysis of data on 135 patients in whom the site of ovulation was documented at the time of surgery and on 24 patients who were studied ultrasonically before surgery indicates that contralateral ovulation and ovum transport occurs in at least a third of ovulatory events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Many studies have shown that the corpus luteal cyst may be located on the contralateral ovary in up to 50% of ectopic pregnancies. [18][19][20] This is due to the method of ovum migration. There are two theories for ovum migration during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that the corpus luteal cyst may be located on the contralateral ovary in up to 50% of ectopic pregnancies. [18][19][20] This is due to the method of ovum migration. There are two theories for ovum migration during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…From here, the ovum may be picked up by either fallopian tube. 7,[18][19][20] This can occur with both ectopic and intrauterine pregnancies. 17,19,21 Ovum transmigration is considered a possible reason for ectopic pregnancy simply due to a delay in implantation.…”
Section: Discussionmentioning
confidence: 99%
“… transperitoneal or transabdominal migration of the oocyte 4 ; aspiration by the contralateral tube of an oocyte that has fallen into the pouch of Douglas 5,6 ; fertilisation in one tube and subsequent migration of the zygote to the uterine cavity and implantation in the contralateral tube 7 . …”
Section: Discussionmentioning
confidence: 99%
“…Since a tubal mass can be located above, below, medial, or lateral to the ovaries, careful attention should be paid to the entire adnexal region. Note that the location of the corpus luteum is not helpful in directing the examination because contralateral implantation occurs in up to one-third of cases (4). When scanning, it can be helpful to perform a gentle bimanual examination by using the probe and a hand on the patient's abdominal wall to move a questionable mass.…”
Section: Techniquementioning
confidence: 99%